Theoretical study of the structural and electronic properties of impurities in non-passivated silicon thin nanowires. (March 2019) - Cruz, F.L. Almeida; Carvalho, A.C.M.; Alves, H.W. Leite
Abstract: In this work, we report theoretical results for the presence of the B, C, N, O and F as impurities in non-passivated [001] thin silicon nanowires. The results for the formation energies show that some dopants tend to segregate to the nanowire surfaces, as observed for passivated [110] ones, but at the double negative charge state. The most stable site for the considered impurities is the interstitial one, where the dopants make bridges with the lateral surface Si atoms, below to this surface, except for the oxygen and fluorine ones, which stay close to the central Si atom. For the neutral carbon, nitrogen and fluorine impurities, the surface π -states located at the facets are filled and a small bandgap appears in the calculated impurity band structures. However, if they were at the double negative charge state, the nanowire metallicity is recovered. Considering the boron and oxygen dopants, the neutral charge state enhances the metallic character at the opposite side of the nanowire where they are, which is reduced when two extra electrons are injected in the system and thus, opening slightly the nanowire bandgap. Our results clearly indicate that doping (or creating vacancies in) these nanowires with acceptors, as well as with hydrogen atoms, can reduce the thin nanowire metallic behavior. Highlights: B, C, N, O and F impurities in non-passivated thin [001] Si nanowires were studied by DFT calculations. Interstitial sites are the most stable one for all the impurities in the double negative charge state. B, C and N tend to segregate to the nanowire surfaces; O and F stay close to the central Si atoms. For neutral C, N and F impurities, the surface π-states located at the facets are filled, and a small bandgap appears but it disappears when these dopants receives two electrons. The neutral B and O impurities enhances the metallic behavior of the nanowire but, after the injection of two electrons, this effect is quite reduced and a small bandgap appears.